The Utilization of Eggshell as Reinforcing Material of Heat Cured Acrylic Resin Denture Base: Pemanfaatan Cangkang Telur Sebagai Bahan Penguat Basis Resin Akrilik Polimerisasi Panas - Syafrinani, Syafrinani; Purba, Sarah Mutiara Beby (TALENTA, 2022)
Heat-cured acrylic resin is easily fractured and can be prevented by adding reinforcing materials of duck eggshell powder. Furthermore, it can be used as a biocompatible reinforcing material due to the high content of CaCO3. This study aims to determine the effect of adding 2.5% and 5% duck eggshells as reinforcement for the denture base with heat-cured acrylic resin on the transverse strength. The method is an laboratory experiments with a post-test only control design conducted on January 2022. The samples were made by adding a reinforcing agent of 2.5% and 5% heat-cured acrylic resin powder’s weight in a mould sized 65 x 10 x 2.5 ± 0.5 mm with 11 samples in each group. The curing process was executed at a temperature of 70°C for 90 minutes before increasing to 100°C for 30 minutes, and the transverse strength of acrylic resin was measured using the Universal Testing Machine. The sample tested using univariate analysis with the results of the average transverse strength in the control group 66.59 ± 1.88 MPa, after adding 2.5% duck eggshell 72.61 ± 3.05 MPa and 5% duck eggshell 86.14 ± 4.09. The one-way ANOVA and LSD tests showed significant results with p-value = 0.001 (p < 0.05) and 0.001 (p <0.05). The highest transverse strength value of heat-cured acrylic resin was found in the 5% duck eggshell group, followed by 2.5%, and lastly, the control group.